2000
DOI: 10.1111/j.1346-8138.2000.tb02229.x
|View full text |Cite
|
Sign up to set email alerts
|

Olmsted Syndrome: Report of Two New Cases and Literature Review

Abstract: Olmsted syndrome is a rare keratinization disorder; 18 cases have been published so far. It associates a mutilating cogenital palmoplantar keratoderma with periorificial erythematokeratotic lesions. We report herein two new unrelated male children with Olmsted syndrome (OS), one of whom was studied by light and electron microscopy. Our histological, immunohistochemical, and ultrastructural findings suggest that this disease is related to epidermal hyperproliferation. We present herein a review of the twenty ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 21 publications
1
44
1
Order By: Relevance
“…Although some authors reported good results with surgery, 10,14,26 full-thickness excision and skin grafting is unreliable because hyperkeratosis may recur at the grafted site and may develop at the donor site as a result of a Koebner phenomenon. Methotrexate 25 and systemic corticosteroids 8,15,19 do not control the lesions. Systemic retinoids appear to be the most promising therapeutic agents.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Although some authors reported good results with surgery, 10,14,26 full-thickness excision and skin grafting is unreliable because hyperkeratosis may recur at the grafted site and may develop at the donor site as a result of a Koebner phenomenon. Methotrexate 25 and systemic corticosteroids 8,15,19 do not control the lesions. Systemic retinoids appear to be the most promising therapeutic agents.…”
Section: Discussionmentioning
confidence: 90%
“…Their study showed a suprabasilar staining pattern with AE1, a monoclonal antikeratin antibody that has specificity for immature keratins, showing only basilar staining in normal skin. Larregue et al 19 also reported abnormal ex- 24 demonstrated that hyperproliferative activity involves the basal and the suprabasal keratinocytes. The inheritance pattern of Olmsted syndrome is unknown.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…11 Surgical removals of affected skin and autografting have also been unsuccessful due to the recurrence problem. [12][13][14][15][16] The hallmarks of OS represent an exceptional case that excludes this disorder from other syndromes of keratoderma. OS shares etiological similarities with symptoms of carcinoma and indeed co-occurrence of squamous cell carcinoma and adenocarcinoma of the lung in certain cases of OS is also reported.…”
Section: Introductionmentioning
confidence: 99%
“…17 OSpatients have higher susceptibility to develop epidermal tumors. 16 All these factors render OS as a clinically important etiology for its uniqueness.…”
Section: Introductionmentioning
confidence: 99%